Unleashing the Potential of Electroactive Hybrid Biomaterials and Self-Powered Systems for Bone Therapeutics - Shichang Liu; Farid Manshaii; Jinmiao Chen; Xinfei Wang; Shaolei Wang; Junyi Yin; Ming Yang; Xuxu Chen; Xinhua Yin; Yunlei Zhou (Nano-Micro Letters)
Highlights Introduce the role of bioelectricity and the endogenous electric field in bone tissue and summarize different techniques to electrically stimulate cells and tissue. Highlight the latest progress in exploring electroactive hybrid biomaterials as well as self-powered systems such as triboelectric and piezoelectric-based nanogenerators and photovoltaic cell-based devices in bone tissue engineering. Emphasize the significance of simulating the target tissue’s electrophysiological microenvironment and propose the opportunities and challenges faced by electroactive hybrid biomaterials and self-powered bioelectronics.